Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the net area between the graph of [tex]\( f(x) = x^3 + 3x^2 - 2x + 3 \)[/tex] and the [tex]\( x \)[/tex]-axis over the interval [tex]\([-2, 2]\)[/tex], we need to evaluate the definite integral of [tex]\( f(x) \)[/tex] from [tex]\(-2\)[/tex] to [tex]\(2\)[/tex].
The definite integral:
[tex]\[ \int_{-2}^{2} (x^3 + 3x^2 - 2x + 3) \, dx \][/tex]
represents the net area.
Let's proceed step-by-step:
1. Set up the integral:
[tex]\[ \int_{-2}^{2} (x^3 + 3x^2 - 2x + 3) \, dx \][/tex]
2. Evaluate the integral:
To integrate each term independently, we find the antiderivative of [tex]\( f(x) \)[/tex]:
[tex]\[ \int x^3 \, dx = \frac{x^4}{4}, \quad \int 3x^2 \, dx = x^3, \quad \int (-2x) \, dx = -x^2, \quad \int 3 \, dx = 3x \][/tex]
Thus, the antiderivative of [tex]\( f(x) \)[/tex] is:
[tex]\[ F(x) = \frac{x^4}{4} + x^3 - x^2 + 3x \][/tex]
3. Evaluate [tex]\( F(x) \)[/tex] at the bounds:
[tex]\[ F(2) = \frac{2^4}{4} + 2^3 - 2^2 + 3 \cdot 2 \][/tex]
[tex]\[ F(2) = \frac{16}{4} + 8 - 4 + 6 \][/tex]
[tex]\[ F(2) = 4 + 8 - 4 + 6 \][/tex]
[tex]\[ F(2) = 14 \][/tex]
[tex]\[ F(-2) = \frac{(-2)^4}{4} + (-2)^3 - (-2)^2 + 3 \cdot (-2) \][/tex]
[tex]\[ F(-2) = \frac{16}{4} - 8 - 4 - 6 \][/tex]
[tex]\[ F(-2) = 4 - 8 - 4 - 6 \][/tex]
[tex]\[ F(-2) = -14 \][/tex]
4. Subtract the values:
[tex]\[ \int_{-2}^{2} (x^3 + 3x^2 - 2x + 3) \, dx = F(2) - F(-2) \][/tex]
[tex]\[ = 14 - (-14) \][/tex]
[tex]\[ = 14 + 14 \][/tex]
[tex]\[ = 28 \][/tex]
So the net area between the graph of [tex]\( f(x) \)[/tex] and the [tex]\( x \)[/tex]-axis over the interval [tex]\([-2, 2]\)[/tex] is [tex]\( 28.0 \)[/tex] (rounded to two decimal places).
Answer:
28.0
The definite integral:
[tex]\[ \int_{-2}^{2} (x^3 + 3x^2 - 2x + 3) \, dx \][/tex]
represents the net area.
Let's proceed step-by-step:
1. Set up the integral:
[tex]\[ \int_{-2}^{2} (x^3 + 3x^2 - 2x + 3) \, dx \][/tex]
2. Evaluate the integral:
To integrate each term independently, we find the antiderivative of [tex]\( f(x) \)[/tex]:
[tex]\[ \int x^3 \, dx = \frac{x^4}{4}, \quad \int 3x^2 \, dx = x^3, \quad \int (-2x) \, dx = -x^2, \quad \int 3 \, dx = 3x \][/tex]
Thus, the antiderivative of [tex]\( f(x) \)[/tex] is:
[tex]\[ F(x) = \frac{x^4}{4} + x^3 - x^2 + 3x \][/tex]
3. Evaluate [tex]\( F(x) \)[/tex] at the bounds:
[tex]\[ F(2) = \frac{2^4}{4} + 2^3 - 2^2 + 3 \cdot 2 \][/tex]
[tex]\[ F(2) = \frac{16}{4} + 8 - 4 + 6 \][/tex]
[tex]\[ F(2) = 4 + 8 - 4 + 6 \][/tex]
[tex]\[ F(2) = 14 \][/tex]
[tex]\[ F(-2) = \frac{(-2)^4}{4} + (-2)^3 - (-2)^2 + 3 \cdot (-2) \][/tex]
[tex]\[ F(-2) = \frac{16}{4} - 8 - 4 - 6 \][/tex]
[tex]\[ F(-2) = 4 - 8 - 4 - 6 \][/tex]
[tex]\[ F(-2) = -14 \][/tex]
4. Subtract the values:
[tex]\[ \int_{-2}^{2} (x^3 + 3x^2 - 2x + 3) \, dx = F(2) - F(-2) \][/tex]
[tex]\[ = 14 - (-14) \][/tex]
[tex]\[ = 14 + 14 \][/tex]
[tex]\[ = 28 \][/tex]
So the net area between the graph of [tex]\( f(x) \)[/tex] and the [tex]\( x \)[/tex]-axis over the interval [tex]\([-2, 2]\)[/tex] is [tex]\( 28.0 \)[/tex] (rounded to two decimal places).
Answer:
28.0
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.